2019
DOI: 10.1002/suco.201800129
|View full text |Cite
|
Sign up to set email alerts
|

Precast reinforced concrete shear walls: State of the art review

Abstract: Expeditious urbanization and population rise around the globe has fostered the need of speedy and efficient construction, thus generating immense pressure on the construction industry to introduce an efficacious construction technique. The issue can be addressed by precast technology, which is advantageous over conventional monolithic construction in regards to speed, safety, and quality control along with reduced construction cost on mass scale production. However, precast reinforced concrete (RC) buildings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 48 publications
(98 reference statements)
0
29
0
Order By: Relevance
“…In the current decade, few types of wall to wall horizontal connections have been introduced to the construction industry such loop connection, wire loop and U-shape steel channel. The structural behaviors of loop connection have been investigated by [2,11,13,17] in terms of anchorage length, bonding and tensile. The section is to shed the light on types of precast wall to wall horizontal connections and their structural behaviours.…”
Section: Types Of Wall To Wall Horizontal Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current decade, few types of wall to wall horizontal connections have been introduced to the construction industry such loop connection, wire loop and U-shape steel channel. The structural behaviors of loop connection have been investigated by [2,11,13,17] in terms of anchorage length, bonding and tensile. The section is to shed the light on types of precast wall to wall horizontal connections and their structural behaviours.…”
Section: Types Of Wall To Wall Horizontal Connectionmentioning
confidence: 99%
“…Furthermore, the joint consists of loop-shaped rebar anchorages into wall panel during casting of precast wall panels and cast in situ concrete to form an integrated wall. As loop shaped bars are protruding out from the connected part of precast wall by lap splicing in the intermediate joint, the connection is activated once the joint is grouted by cast in situ concrete or mortar [11]. The purpose of loop-shaped anchorage is to decrease the length of lapping rebar [2].…”
Section: A Loop Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing growth of precast construction, it is often looked upon with skepticism due to lack of knowledge about its seismic behavior. 1 Failure of connections, insufficient diaphragm action by precast slabs and roof system, insufficient ductility of columns are often the major causes of failure of precast buildings during earthquake. [2][3][4] Generally, precast beams and columns are connected with dry moment-resisting connections, castin-place and welded connections.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the relatively large in‐plane depth of the wall members, a considerable lateral stiffness, strength and deformation capacity are provided. Recent investigations have revealed that precast structural systems can effectively reduce carbon emissions, waste generation, onsite frameworks and labor, and construction time cycles and improve quality control to a certain extent 1–3 . PC members are manufactured in standardized factories, installed in construction sites, and assembled via liable connections.…”
Section: Introductionmentioning
confidence: 99%